Indifference in economics: Between praxeology and the neoclassical presentation of a consumer’s choice - Wojciech Giza (International Entrepreneurship Review)
Objective: The objective of the article is to present the differences in the research approach concerning consumer behaviour from the perspective of neoclassical economics and the Austrian school of economics.